ANALYSIS OF TOURIST PERCEPTIONS IN SITU BAGENDIT BASED ON THE 6A TOURISM COMPONENTS - Anggraeni, Yuni (SABA: Journal of Tourism Research, 2024)
Situ Bagendit it is one of tourist attraction often visited by tourist. Situ Bagendit increased in the of number visits after there is new renovation compared to before. However, in its development by the Tourism and Culture Office of Garut Regency Government., Situ Bagendit there are still shortcomings such as petrol station, parking place, and toilet. With these problem then it is necessary to conduct research on tourist perception based on tourism component 6A (Attraction, Accessibility, Amenities, Ancillary Service, Accommodation and Activity). Besides that, benefit from conduct research for The Tourism and Culture Office of Garut Regency Government. to pay more attention facilities and improved quality Situ Bagendit in the future. The methode used in this study that is quantitative methodes with purpose sampling. This is research distributing questionnaire with the sample 100 respondents. The results of this analysis obtained form the results minimum, maximum, mean and respondent achievement level. The result obtained by the authors indicate that tourist perception of attraction, accessibility, and amenities are in the quite good. Tourist perception of ancillary service are in the poor category. Finally tourist perception of accommodation and activity are in the quite good.